Process of Contracting Hashtags in Modern Virtual Communication - A. V. Alekseev (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The article is devoted to the study of language compression, presented in one lexical unit at two different levels: graphic and semantic. The relevance of the study is due to the need to understand the basic social and political processes presented in the texts of modern virtual communication in order to identify the most important events at the present stage of development of society through linguistic analysis. The novelty of the study is that the analysis of hashtags in the English language is carried out for the first time from the perspective of the contraction process, examples of such linguistic facts are presented. Particular attention is paid to the processes of deciphering hashtags in the English language and the explication of the reduced lexical unit in the target language. It is emphasized that the principle of saving speech effort is most common in the texts of modern virtual communication. The question of the translingual aspect of the functioning of English-speaking hashtags that are subject to the process of contraction in speech is considered. Using statistical analysis, two main ideas have been proved regarding the linguistic nature of these language units: the contraction process is formative when they are created; the use of contracted hashtags in political texts seems to be a common and natural phenomenon in virtual discourse.